Assessment of subchronic toxicity of fermented Houttuynia Cordata thunb. Using rodent model system - Chaiyavat Chaiyasut (2018)
© 2018 The Authors. Published by Innovare Academic Sciences Pvt Ltd. Objective: The present study was intended to evaluate the subchronic toxicity of Lactobacillus-mediated fermented Houttuynia cordata juice (FHJ) using rodent model system. Methods: FHJ was prepared and the microbial load, lactic acid content, and pH was estimated. Rats were fed with different doses of FHJ for 60 days. The body mass changes were measured during FHJ supplementation. After the treatment period, blood and organs of the experimental rats were collected. The samples were subjected to hematological and biochemical analysis by following standard hospital protocols. Results: The pH of FHJ after 30 days of fermentation was 3.63. The lactic acid content of FHJ was gradually increased and reached 19.70 mg per mL after 30 days of the fermentation process. Lactobacillus load was high in FHJ after 30 days and no Bacillus spp. and yeast were detected in FHJ at any point of fermentation. There were no significant changes in body weight of male and female experimental rats supplemented with FHJ, irrespective of dose. There were no significant treatment-related pathological changes found in any organ of the experimental rats at all tested dose levels when compared with organs in control animals. There were no significant changes observed in red blood cells (RBCs), white blood cells (WBCs), hemoglobin, hematocrits, lymphocyte, and platelets level of male rats of all groups. Whereas, significant (p<0.01) changes were observed in the RBC (1.02±0.26 106/mm3) of female rats in effective dose (ED) group compared to control. Similarly, significant (p<0.01) changes were detected in the WBC level of female rats in high dose (−7.53±0.03 103/mm3), and post-ED group (−8.86±0.75 103/mm3) compared to control. There were no alterations in tested biochemical parameters of experimental rats. Conclusion: The FHJ was rich in probiotic Lactobacillus. The supplementation of FHJ (9 mL/kg/day) for 60 days did not significantly affect the body mass, internal organs, hematological, and biochemical parameters of rats. The results suggested that FHJ is qualified for the human consumption.